Histopathological effect of co-administration of efavirenz and vitamin E on the liver, and biochemical parameters in wistar rats - Peter, Aniekan I; Edagha, Inocent A (Asian Journal of Medical Sciences, 2016)
Background: Efavirenz is a drug used in combination as highly active antiretroviral therapy (HAART) used for the treatment of human immunodeficiency virus (HIV). Aims and Objectives: To investigate the effects of Efavirenz and vitamin E on the histopathology and biochemical parameters in the liver of Wistar rats. Materials and Methods: Twenty five Wistar rats were divided into fi ve groups. Group A were administered with 1 ml of distil water; group B animals were administered with 8.57 mg/kg Efavirenz, group C were administered with 17.14 mg/kg Efavirenz; group D were administered with 8.57 mg/kg, Efavirenz and 14.82 mg/kg Vitamin E, and group E were administered with 14.82 mg/kg Vitamin E for 32 days. On day 33, the rats were sacrificed using chloroform inhalation method. The liver were excised, routinely processed, stained using haematoxylin and eosin method, and viewed in DPX medium under light microscope. Blood samples from the rats were collected and then centrifuged after 30 minutes to obtain the serum for analysis of aspartate amino transaminase (AST), alanine amino transaminase (ALT), alkaline phosphatase (ALP), and total bilirubin (TB). Results: The liver of Wistar rats administered with Efavirenz, showed distortions with various degree of vacoulations, dilatation of sinusoidal spaces and nuclei pyknoctic changes. In the group where Efavirenz was combined with vitamin E this changes were ameliorated. This also agreed with the biochemical changes which showed significant levels of increase in AST and ALT in Efavirenz groups, this changes were also ameliorated in the group that Efavirenz was combined with vitamin E. Conclusion: Efavirenz administration can damage the liver, vitamin E can ameliorate this effect, therefore Vitamin E should be prescribed for patients on Efavirenz administration. Asian Journal of Medical Sciences Vol.7(5) 2016 81-86